Parental and romantic attachment in adolescents - Matos, Paula Mena (2006)
Based on Bowlby’s and Ainsworth’s attachment theory, ando n Bartholomew’s conceptual and methodological approach, this paper adresses parental and romantic attachment representations of late adolescentes. Using a cross-sectinal research design, the study examines (a) continuities and discintinuities across relational domains, and (b) diferences in attachment representations as a function of adolescent’s and parental gender. Two coded semistructured interviews (Family Attachment Interview and Peer Attachment Interview de Bartholomew & Horowitz, 1991) were administrated to a sample of 82 late adolescentes. Results indicate the presence of regularities in the attachment representations of both domains, evidenced in the thematic and content recurreces of the narratives’ organization. Albeit the moderate magnitude of the values observed, adolescentes with secure attachments to parents tend to relate in a more secure way to their romantic partners, presenting more positive representations of self and others. No gender diferences in attachment patterns were observed, although attachment to mother was classified as more preoccupied for boys and girls, and attachment to father as more dismissive only for boys. DOI: http://dx.doi.org/10.17575/rpsicol.v20i1.379